DETERMINING A SUFFICIENT DEPTH OF PILE FOUNDATION ON THE PERTAMINA GRAVING DOCK DESIGN SORONG PAPUA - Franto Novico (Marine Geological Institute of Indonesia, 2009)
Engineering geological aspect and bearing capacity of pile foundation are significant for safety of upper structure, especially for substantial constructions such as a docking ship. Moreover, it provides effectiveness and cost efficiency when applies in rural areas of Indonesia. This is due to lack of docking ship appropriately built at rural areas particularly in eastern areas of Indonesia. Karim island of Papua even though is a small island yet is very strategic as Pertamina place its transitory function on that island connecting its oil supply route to Sorong. Appropriate docking ship construction is required to aim the effective and efficient port management. Choosing the most suitable structure for a docking is also the key. Graving dock structure has been chosen by Pertamina as the most appropriate type of structure for the docking ship in Karim Island. The structure of graving dock planned to be built in Karim island Papua, is projected to be able to serve the maximum 7500 DWT ship capacity, with approximately dimension is 125 x 25 x 8 meters. Therefore, to support the plan, type and design of the best foundation is the key. There are two methods could be done in determining the type and bearing capacity foundation. Field and laboratory test applied ASTM, field observation result by applying Meyerhoff theory and laboratorial analysis derived from Tarzaghi theory. Those observation and analysis has confirmed that the soil layer at the graving dock design consists of three layers, those are; cover layer, silt-clay layer and clay rock unit. Therefore, the most suitable foundation to be constructed in that area is a pile massive foundation, with depth of pile foundation approximately -20 m below the land surface, and the ultimate point load pile massive for 30x30 cm – 75x75 cm dimension approximately 79.76 – 406.25 ton, and frictional resistance value approximately 24.59 – 61.48 ton. Keyword : Pile Pondation, bearing capacity, Graving dock Aspek geologi teknik dan besarnya nilai kapasitas suatu pondasi tiang pancang merupakan suatu hal yang sangat penting demi keamanan pembangunan struktur bagian atas, khususnya untuk bangunan yang besar dan tinggi. Pembuatan dok kapal menjadi tuntutan yang tak bisa dielakkan demi terlengkapinya manajemen pelabuhan yang efektif dan efisiensi pada daerah yang terpencil. Bangunan graving dock kapal yang direncanakan pada Pulau Karim Papua, diproyeksikan untuk dapat melayani kapal dengan kapasitas maksimal 7500 DWT, dengan dimensi berkisar 125 x 25 x 8 meter. Jenis dan perencanaan pondasi yang tepat sangat penting guna menunjang keamanan bangunan graving dock itu sendiri. Metoda yang digunakan untuk mengetahui jenis pondasi dan daya dukung pondasi didapat dari hasil uji lapangan dan laboratorium. Pengujian lapangan dan laboratorium berdasarkan ASTM, analisis data lapangan mempergunakan metoda Mayerhoff sedangkan analisis data laboratorium mempergunakan metoda Terzaghi. Lapisan tanah pada rencana graving dock terdiri dari tiga bagian yaitu; lapisan penutup, lempung lanauan dan satuan batuan lempung. Untuk itu jenis pondasi yang dipilih adalah pondasi tiang pancang massif. Kedalaman pemancangan pondasi berkisar -20m dari muka tanah. Hasil analisis menunjukkan kuat tekan tiang pancang massif untuk diameter 30x30 cm hingga 75x75 cm berkisar 79.76 – 406.25 ton, sedangkan untuk nilai tarik berkisar dari 24.59 hingga 61.48 ton. Kata Kunci : Tiang pancang, nilai kapasitas, Graving dock